2005
DOI: 10.1007/s11251-004-7686-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating writing instruction through an investigation of students? experiences of learning through writing

Abstract: Learning through writing is a way of learning not only the appropriate written expression of disciplinary knowledge, but also the knowledge itself through reflection and revision. This study investigates the quality of a writing experience provided to university students in a first-year biology subject. The writing instruction methodology used is Genre-based literacy pedagogy, designed to help both with learning disciplinary knowledge and its appropriate written presentation. Evaluative research methodologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
16
0
2
Order By: Relevance
“…Accordingly, the marker is advising the student to use a dictionary to fix spelling errors and for improving vocabulary. This could attest to the fact that students delay writing assignments to the last minute to an extent that they submit poor quality work (Ellis, Taylor & Drury, 2005;Gambell, 1991).…”
Section: "Please Note That Tasks 2and3 Was Supposed To Be Submitted As mentioning
confidence: 99%
“…Accordingly, the marker is advising the student to use a dictionary to fix spelling errors and for improving vocabulary. This could attest to the fact that students delay writing assignments to the last minute to an extent that they submit poor quality work (Ellis, Taylor & Drury, 2005;Gambell, 1991).…”
Section: "Please Note That Tasks 2and3 Was Supposed To Be Submitted As mentioning
confidence: 99%
“…In the case of writing learning journals, a nonalgorithmic worked-out example can be provided in the form of an example of a well-written learning journal, showing the critical features that make a learning journal well written (e.g., wellorganised, including many examples, high amount of metacognitive statements, etc.). Research revealed that learning from written examples or learning by observing a model performing a writing task proved to be successful (see Braaksma, Rijlaarsdam, & van den Bergh, 2002;Ellis, Taylor, & Drury, 2005;Graham & Perin, 2007). For example, Couzijn (1999) found with regard to 9th graders that learning-to-write argumentative texts by observing a model was superior to a learning-by-doing condition.…”
Section: Instructional Support To Overcome Mediation Deficienciesmentioning
confidence: 99%
“…Teaching both styles of academic writing supports Bean's (2011) argument that the most intensive and demanding tool for eliciting sustained critical thought is a welldesigned writing assignment on a subject matter problem. That nexus between writing, disciplinary content and learning is essential (Ellis, Taylor, and Drury, 2005): "[…] research into student writing at university has shown that the experience of writing not only helps students to become familiar with the standards and style of written expression expected in their disciplines, but it also helps them to clarify their understanding of the subject matter about which they are writing". (p. 49-50) Teaching a 'popular' writing genre, therefore, is a relatively small change within the broader picture.…”
Section: Discussionmentioning
confidence: 99%